The political role of Muslim women between traditional texts and changing realities - Osmani, Noor Mohammad; Ali, Md. Yousuf; Ahmad, Abu Umar Faruq (2010)
The Muslim scholars are in general agreement that women are not entitled to hold the topmost public office of a nation. Is that due to certain provisions in the Qur'an and Prophetic traditions (ahadith) or due largely to socio-cultural and economic settings of a country? The Qur'an urges women not to make dazzling display publicly as practiced during Jahiliyyah (33: 33). It also asserts that men are the protectors and maintainers of women (4: 34). The Prophetic tradition commonly cited in this regard is the saying attributed to him which proclaims: "No nation will ever prosper if a woman is assigned to its highest public office." (Bukhari, no. 4073, 6570). On the other hand, the Qur'an acclaims the Queen of Sheba for her just rule. Hence, some prominent scholars such as Imam Abu Hanifah, Tabari and Ibn Hazm support that women could hold the topmost judicial position. Ibn Hazm also asserts that in principle, it is conceivable that women can carry out the mission of Prophethood, and if they could be Prophets, they would also be leaders, for the Prophets are leaders. The present research is carried out to deal with this issue. It would primarily depend on the Qur'anic ayat, Prophetic traditions, heritage of Islamic Caliphs and the verdicts of Muslim jurists. The research will critically evaluate the validity of the quoted hadith, and examine the circumstances surrounding the said hadith to know its real intention. It would also shed light on the present day realities that a significant number of Muslim women successfully led their nations to prosperity and success, through holding topmost offices. The research reached conclusions that there is no explicit text in the Qur’an or Hadith of the Prophet that prohibit women from holding topmost public office. It is her quality, credibility and virtuousness that matter, and not her gender, for being qualified for the highest public office.